Has the time come for excess profit taxes? - Shafik Hebous (CESifo GmbH, 2023)
Excess profit taxes (EPTs) emerge as an option to contribute to the extra needed revenues, avoiding a general increase in corporate tax rates, while having the prospect to serve as a gateway to converge toward a permanent efficient rent tax instaed of the corporate income tax. General unilateral (temporary or permanent) EPTs would face the same international pressures from profit shifting and tax competition as the existing corporate income tax, calling for international coordination. A coordinated EPT on multinational enterprises can take the form of a formulary apportionment approach that allocates the EPT base using sales by destination.
Keywords: 330; Residualgewinn; Ertragsbesteuerung; Ökonomische Rente; Multinationales Unternehmen; Steuerharmonisierung; Konzernbesteuerung; Welt